Multi-Mode-Cavity-Resonator-Based Bandpass Filters With Multiple Levels of Transfer-Function Adaptivity - Dimitra Psychogiou (IEEE Access, 2019)
This paper reports on dual-mode-cavity-resonator-based bandpass filters (BPFs) with multiple levels of transfer-function tunability. They are based on substrate-integrated-waveguide cavity resonators that are loaded by four identical metallic posts and give rise to two degenerate modes that are exploited for the filter design. By loading the ends of the posts with variable-reactance elements, quasi-elliptic-type filtering transfer functions with multiple levels of spectral adaptivity can be obtained. These reconfiguration properties include center-frequency control, bandwidth tuning, and intrinsic RF switching-off. The proposed adaptive BPF concept can be extended to high-order transfer functions shaped by 2N poles and $2N$ transmission zeros (TZs) for BPFs composed of N dual-mode resonators. To prove the experimental viability of the engineered tunable BPF concept, a two-pole/two-TZ prototype and a four-pole/four-TZ prototype with tunable transfer functions in the 1.5-3 GHz band were built and measured.